Analisis Manajemen Pembelajaran Guru Bahasa Indonesia di Sub Rayon Sekolah Menengah Atas Negeri 12 Palembang - Dewi, Yusmala; Syuroh, Mat; Febrianza, M. (@-Publik: Jurnal Administrasi Publik, 2023)
According to Law No. 20 of 2003 on the National Education System, education functions to develop abilities, form character, and civilize a dignified nation in order to educate the nation's life. The government is always making improvements and developing quality in the national education system. One of the government's efforts is to change the curriculum from KTSP to Curriculum 2013. The curriculum is implemented by utilizing natural, social and cultural conditions and regional wealth for educational success with optimal content of all study materials. Indonesian Language Teachers in the Sub Rayon SMA Negeri 12 Palembang have managed the Indonesian Language Curriculum, but still experience obstacles. Based on the results of pre-research interviews, it is known that, in preparing and managing Indonesian Language Learning tends to deal with several problems related to ignorance and the tendency to ignore this management. The purpose of this research is to analyze Indonesian Language Teacher Learning Management in Sub Rayon SMA Negeri 12 Palembang. This research uses a qualitative approach with a descriptive level of explanation. Based on the results of research and discussion of the results of the study it can be concluded that the Learning Management of Indonesian Language Teachers in the Sub Rayon SMA Negeri 12 Palembang is quite optimal even though it still experiences some obstacles. In the formulation of Indonesian Language Teachers Learning Management Plan in Sub Rayon SMA Negeri 12 Palembang, it has been done well which is carried out in the form of training groups for Indonesian language teachers through MGMP activities. However, Indonesian Language Teachers in SMA Negeri 12 Palembang do not have a vision, mission, and goals in Indonesian language learning in writing. Based on the dimension of Controlling, Monitoring Learning Management of Indonesian Language Teachers in Sub Rayon SMA Negeri 12 Palembang, it is known that there is still a lack of supervision and monitoring from superiors in this case the principal and the curriculum section in terms of implementing workshops and in house training for Indonesian language teachers so that they understand about Indonesian language learning management.